Exploring the role of vocabulary depth and semantic set in EFL learners’ vocabulary use in writing - Mahmood Reza Atai; Ali Dabbagh (Teaching English Language, 2010)
The role of depth of vocabulary knowledge in EFL writing performance has remained an under-researched issue. The present study was designed to investigate the role of depth of vocabulary knowledge and semantic set in making appropriate word choices in EFL learners’ writing performance. Participants were 70 lower-intermediate and upper-intermediate EFL learners. Instrumentation included Oxford Quick Placement Test, Word Association Test (WAT), and two writing tests. The results of MANOVA and independent t-tests revealed that: a) depth of vocabulary knowledge played a fundamental role in appropriate use of words in a semantic set in lower-intermediate level but not in upper-intermediate level, b) depth of vocabulary knowledge had a significant role in overall writing performance only in upper-intermediate level, c) using words appropriately in a semantic set played a significant role in writing performance of the lower-intermediate participants, while the opposite was found for the upper-intermediate group. The results may promise implications for vocabulary and writing curriculum development and instruction.